Building a Culture of Authentic Partnership: One Academic Health Center Model for Nursing Leadership. (September 2017) - Heath, Janie; Swartz, Colleen
Abstract : Senior nursing leaders from the University of Kentucky (UK) College of Nursing and UK HealthCare have explored the meaning of an authentic partnership. This article quantifies the tangible benefits and outcomes from this maturing academic nursing and clinical practice partnership. Benefits include inaugural academic nursing participation in health system governance, expanded integration of nursing research programs both in the college and in the health science center, and the development of collaborative strategies to address nursing workforce needs.